1980
DOI: 10.1007/bf00964786
|View full text |Cite
|
Sign up to set email alerts
|

16 S acetylcholinesterase in endplate-free regions of developing rat diaphragm

Abstract: Velocity sedimentation patterns of acetylcholinesterase (AChE, EC 3.7.1.1) in endplate-free regions of the diaphragm were studied in rats during early postnatal development. A significant amount of 16 S AChE, comprising 20% total activity, was found in endplate-free regions of the diaphragm of 8- and 19-day-old rats. By 32 days after birth, 16 S AChE accounted for less than 5% total AChE activity in endplate-free regions. 16 S AChE is, therefore, not strictly an endplate-specific molecular form. Instead, it be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…In the rat, 26 to 40% of the AChE activity is associated specifically with endplates; the balance is distributed throughout the muscle as nonendplate enzyme (Hall, 1973;Vigny et al, 1976;Younkin et al, 1982). The nonendplate enzyme in rat skeletal muscle is composed almost entirely of globular 10 S (G4) and 4 S (G1) forms (Hall, 1973;Vigny et al, 1976;Bon et al 1979;Younkin et al, 1982), although asymmetric forms clearly comprise a small component of the nonendplate AChE in the rat diaphragm (Sketelj and Brzin, 1980;Younkin et al, 1982). The asymmetric forms of AChE are of particular interest because they are highly concentrated in the endplate region of adult rat skeletal muscle (Hall, 1973;Vigny et al, 1976;Younkin et al, 1982) and appear to comprise virtually all (at least 84%) of the external AChE that is associated specifically with endplates (Yom&in et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, 26 to 40% of the AChE activity is associated specifically with endplates; the balance is distributed throughout the muscle as nonendplate enzyme (Hall, 1973;Vigny et al, 1976;Younkin et al, 1982). The nonendplate enzyme in rat skeletal muscle is composed almost entirely of globular 10 S (G4) and 4 S (G1) forms (Hall, 1973;Vigny et al, 1976;Bon et al 1979;Younkin et al, 1982), although asymmetric forms clearly comprise a small component of the nonendplate AChE in the rat diaphragm (Sketelj and Brzin, 1980;Younkin et al, 1982). The asymmetric forms of AChE are of particular interest because they are highly concentrated in the endplate region of adult rat skeletal muscle (Hall, 1973;Vigny et al, 1976;Younkin et al, 1982) and appear to comprise virtually all (at least 84%) of the external AChE that is associated specifically with endplates (Yom&in et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In rat and mouse, numerous studies have shown that the expression and distribution of AChE forms in muscles depend on age, on the fast or slow type of muscle, and on activity (Sketelj and Brzin, 1980;Lømo et al, 1985;Toutant and Massoulié, 1988). During development, AChE T transcripts in muscle fibers accumulate beneath the synaptic contacts as soon as they are established (Legay et al, 1995).…”
mentioning
confidence: 99%
“…When rat muscle, for example, is chronically denervated in vivo, AChE decreases both in total content and in the form (16 S) suggested to be endplate-specific (Hall, 1973 ;Vigny, Koenig and Rieger, 1976 ;Sketelj and Brzin, 1980 .…”
mentioning
confidence: 99%
“…However, such analysis after gross excision of endplate-rich zones does not exclude the possibility that some other forms are present, both inside and outside the endplate. Further, the specific association of H 2c with the endplates has been questioned after similar experiments on human (Carson et al, 1979) and immature rat (Sketelj and Brzin, 1980) fig. 1 C, which shows that both the amount of AChE and the pattern of its forms is the same in dystrophic and normal birds.…”
mentioning
confidence: 99%